PENGGUNAAN MEDIA PEMBELAJARAN MEDIA REALITAS VIRTUAL DAN REALITAS AUGMENTASI PADA MATA KULIAH PRAKTIK BATU BETON - Shendy Oktaviani (ADISAM PUBLISHER, 2024)
In an era that continues to develop, there are challenges that will be faced by the existing education system in Indonesia. Education needs to continue to adapt to keep up with changes in the world. In all types of technology that stands out in education is virtual reality media and augmented reality. This research uses qualitative research with a literature study method. The implementation of virtual reality in education has become a major focus in efforts to improve students' holistic augmented reality learning experience. The implementation of augmented reality in education has opened the door to a more interactive augmented reality learning experience and presented the potential of augmented reality to increase student understanding and engagement. The use of virtual reality media and augmented reality in learning contexts has shown great potential to enhance student learning experiences and expand boundaries. -traditional boundaries in education. By adopting a collaborative approach between educational institutions, the technology industry, and government, and through investment in training and professional development for educators.